Efektivitas Model Discovery Learning Berbantuan Media Mibolokus Terhadap Pemahaman Konsep IPAS SD - Hakiki, Hafidhotun; Hilyana, F. Shoufika; Ardianti, Sekar Dwi (Educatio, 2025)
A learning process that is monotonous and always centered on the teacher can cause students' low understanding of concepts. This can be proven by the reality found at SD 4 Honggosoco. Based on the initial concept understanding test carried out by 20 class V students, it was found that all students' scores were still below the KKTP with an average class score of 20.05. The aim of this research is to find out whether the Discovery Learning model assisted by Mibolokus media has an effect on the results of students' understanding of concepts at SD 4 Honggosoco in science material. This research uses a quantitative type of research. The research design used was a pre-experiment design with one group pretest posttest type. The subjects of this research were all fifth-grade students at SD 4 Honggosoco with a sampling technique using nonprobability sampling, purposive sampling type. Data collection was carried out by interviews, observation, tests (pretest and posttest), and documentation. The data analysis techniques used are Normality Test, Paired Sample T-Test and N-Gain Test. The results of the Paired Sample T-Test show a significance of 0.000, which means Ho is rejected and Ha is accepted. Meanwhile, the N-Gain Test results were 75.4%, which means that increasing students' understanding of concepts can be categorized as quite effective. The conclusions from this research are: (1) There is a significant difference in the average score in the results of students' conceptual understanding before and after being treated in the form of the Discovery Learning model assisted by Mibolokus media. (2) there is an increase in the results of students' understanding of concepts using the Discovery Learning model assisted by Mibolokus media in the Class V Social Sciences Subject Chapter 1 Properties of Light and Sound.